Factors Affecting Sovereign Debt: Inflation, Repayment of Foreign Debt of the Previous Year, and Exchange Rate - Anita Meilani; Cris Kuntadi (Dinasti International Journal of Education Management And Social Science, 2022)
Purpose-Reasons why inflation, repayment of the previous year's foreign debt, and exchange rate build a hypothesis of the influence between variables so that it can be utilized and used in subsequent research. Design/methodology/approach-The results of the literature review article that the author has done show that there is an influence of the inflation variable on sovereign debt, the effect of foreign debt payments in the previous year on variable sovereign debt, and there is an influence of the exchange rate variable on the variable sovereign debt. Findings-specificity applies to countries estimated results suggest that factors affecting sovereign debt. Originality/value-This research paper reviews the factors that affecting sovereign debt as a dependent variable, inflation, repayment of the previous year's foreign debt, and exchange rate as independent variables.